A cointegration analysis on the effect of exchange rate on energy consumption and economic growth in the Philippines - Angulo, Alyssa Raine Rose (Animo Repository, 2022)
The Philippines is heavily dependent on importing energy sources to meet the country’s energy demand, making energy consumption and economic growth sensitive to exchange rate fluctuations. Based on the economic model developed by Wang, Yu, Zhang, and Chen (2021), this study used a cointegration model to analyze the effect of real effective exchange rate (REER) on energy consumption and economic growth. Following the Cobb-Douglas production function, the variables capital stock and labor input were also added to the model. Using Philippine annual data from 1981 to 2019, this study confirmed that the effect of total energy consumption on economic growth follows a linear cointegration represented by the vector error correction model (VECM) when REER is added to the model. Meanwhile, the model using only coal energy consumption follows a two-regime self-exciting threshold autoregressive (SETAR) model when REER is included.